Editorial: Applied Computing 2023 - Yousra Abdul Alsahib S. Aldeen; Yusliza Yusoff; Samira Naji Kadhim (مجلة بغداد للعلوم, 2024)
Applied computing utilizes aspects of computer science to solve problems in several disciplines, including business, politics, education, and the environment. Occupied in this field, it will likely use a range of programming, graphic applications, networking, software engineering and operating systems management skills to collect, analyze, store, and deliver information that will help resolve issues for individuals, companies, and groups. Applied computing is the study of both applied computer science and theoretical. Thought the intersection of information technology, computer science, and business, applied computing focuses on technical computing concepts and the occurrence of skills in organizational leadership and business strategy.  It can be classified the applied computing skills and knowledge into (Current programming languages and technology, Software engineering, IT security, Mobile technology, Networking, Operating system management, Graphic applications, Data integration, Distributed systems, Communication, Critical thinking, analysis, and problem-solving, Project management). Feasibly the most defining characteristic of applied computing is the ability to assume critically about how to best use their technical skills to problem solve and make a positive impact on the organization. This special issue of Baghdad Science Journal on applied computing provides an overview of applied computing for Current programming languages and technology, Software engineering, IT security, Mobile technology, Networking, by publishing articles on recent research concepts.